PENGARUH LINGKUNGAN ORGANISASI, STRESS KERJA DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN PADA PT. SEMPURNA SEJAHTERA - Yunita Fitri Wahyuningtyas; Syaiyi Datul Munauwaroh (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2022)
The purpose of this study was to analyze the effect of the level of organizational environment, job stress and job satisfaction on employee turnover intention at PT. Sempurna Sejahtera. The sampling method used was saturated sampling technique. The sample in this study were employees of PT. Sempurna Sejahtera with a total sample of 60 respondents. The analytical method used is multiple linear regression analysis. The results of this study indicate that the organizational environment does not have a significant positive effect on turnover intention. The value of tcount less than ttable is 0.139 less than 2,000 with the results of a partial statistical analysis (t test) a significance value of 0.890 greather than 0.05. Work stress has a positive and significant effect on turnover intention. The value of tcount greather than ttable is 2,324 greather than 2,000 with the result (t test) a significance value of 0.024 less than 0.05. Job satisfaction has a negative and significant effect on turnover intention employee. The value of tcount less than ttable is -1.771 less than 2,000 with the result (t test) a significance value of 0.024 less than 0.05. Based on the test results F Fcountgreather than Ftable or 16.048greather than 2.77 and significant level of 0.000 less than0.05 and coefficient of determination (R2)obtained was 0.433, which means the Environment Organization, Job Stress and Job Satisfaction significant effect on Turnover Intention employee by 43.3% and the remaining 56.7% is influenced by other variables not examined.